Patricio Cariola Barroilhet and His Contribution to the Pedagogical Renewal in the Second Half of the 20th Century in Chile [Patricio Cariola Barroilhet y Su Aporte a la Renovación Pedagógica en la Segunda Mitad del Siglo 20 en Chile] - Caiceo-Escudero, J (Associacao Sul Rio Grandense de Pesquisadores em Historia da Educacao, 2015)
The aim is to present some biographical background of Patricio Cariola and highlight his pedagogical contributions to Chilean and Latin American education. His main work focuses on the founding of a centre of research and development education-Cide-the most significant in Latin America. From this point, his concern especially during the military dictatorship in Chile, was to raise resources to investigate the Chilean educational reality and propose policies for the future, obtain an agreement with the University of Leuven in Belgium for many Chileans who could doctorate in Social Sciences and Education and create a network of researchers throughout Latin America, and spread their results.
Keywords: Educational improvement; Educational research; Innovative education; National education awards